2022
DOI: 10.1002/humu.24454
|View full text |Cite
|
Sign up to set email alerts
|

Mosaicism in tuberous sclerosis complex: Lowering the threshold for clinical reporting

Abstract: Tuberous sclerosis complex (TSC) is a multi-system genetic disorder. Most patients have germline mutations in TSC1 or TSC2 but, 10%-15% patients do not have TSC1/TSC2 mutations detected on routine clinical genetic testing. We investigated the contribution of low-level mosaic TSC1/TSC2 mutations in unsolved sporadic patients and families with TSC. Thirty-one sporadic TSC patients negative on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Mirroring UDP-Vic [22], families were considered solved when a molecular diagnosis in an established disease gene was made, or when a strong candidate for novel gene discovery was identi ed. For molecular diagnoses in established disease genes, the variant needed to reach criteria for the American College of Medical Genetics and Genomics (ACMG) classi cation of pathogenic or likely pathogenic (P/LP) [39]. For novel disease-gene variants and new phenotypes in known disease genes, we adopted the same 'strong candidate diagnosis' approach as UDP-Vic [22].…”
Section: Report Generation and Return Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mirroring UDP-Vic [22], families were considered solved when a molecular diagnosis in an established disease gene was made, or when a strong candidate for novel gene discovery was identi ed. For molecular diagnoses in established disease genes, the variant needed to reach criteria for the American College of Medical Genetics and Genomics (ACMG) classi cation of pathogenic or likely pathogenic (P/LP) [39]. For novel disease-gene variants and new phenotypes in known disease genes, we adopted the same 'strong candidate diagnosis' approach as UDP-Vic [22].…”
Section: Report Generation and Return Of Resultsmentioning
confidence: 99%
“…Somatic variants in the KMT2C gene are often identi ed in renal cell cancer [47]; however, none of the families reported with germline alterations in this gene have had renal cancer. This variant is classi ed as pathogenic according to the ACMG criteria [39] (PVS1, PM2, PS2).…”
Section: Kmt2c (Ah016)mentioning
confidence: 99%
“…Namely, those with higher VAF in clinically accessible samples were more likely to present with a greater number of TSC features [ 105 ]. However, the opposite was found in another study of 31 NMI TSC patients, where blood, saliva, and buccal VAF in the 16 mosaic patients were not associated with the number of major clinical features [ 106 ]. Yet, the study did find that VAFs from saliva and buccal samples correlated with tuber load.…”
Section: Updates To Genotype–phenotype Correlations In Tsc: Mosaicism...mentioning
confidence: 89%
“…However, it is unclear whether mosaicism in isolated brain cell populations or even lower VAFs in the brain cause MCD or associated symptomatology [ 66 ]. In clinically accessible samples, VAFs do not always correlate with those in affected tissue such as the brain, as organs affected depend on the embryonic lineage affected as well as the timing of the initial variant [ 65 , 106 , 109 , 110 , 111 ]. This can be exemplified by a case study in which two individuals with TSC2 VAFs of ≤25% in blood showed severe, multiorgan TSC phenotypes [ 112 ].…”
Section: Updates To Genotype–phenotype Correlations In Tsc: Mosaicism...mentioning
confidence: 99%
“…Newborn screening has successfully begun to provide an early diagnosis, even before the presentation of symptoms (Qiao et al., 2021; Su et al., 2021). However, in 10%–15% TSC patients there is no pathogenic variant identified in either TSC1 or TSC2 genes based on standard clinical testing and are generally attributed to low mosaicism, deep intronic/promoter variants, and additional causative gene loci yet to be identified (Brook‐Carter et al., 1994; Curatolo et al., 2008; Klonowska et al., 2023; Sancak et al., 2005; Ye et al., 2022). For instance, in one study, undetected somatic mosaic variants were the most common cause for undiagnosed patients with TSC with up to 51.6% (16/31) of undiagnosed patients being found to carry a disease‐causing mosaic variant (Ye et al., 2022).…”
Section: Discussionmentioning
confidence: 99%